The effects of high-sulfate water and Zeolite (Clinoptilolite) on nursery pig performance - J R Flohr; N W Shelton; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 320 nursery pigs (PIC 1050 barrows) were used in a 24-d study to determine the effects of high-sulfate water and dietary natural zeolite on growth performance and fecal consistency of nursery pigs. Eight treatments were arranged as a 2 × 4 factorial with 2 water treatments (control or water with 3,000 ppm sodium sulfate), and 4 dietary zeolite concentrations (0, 0.25, 0.5, and 1.0%). Water treatments remained the same from d 0 to 24 and all diets were fed in 2 phases, with diets containing zeolite having the same inclusion rate in both phases. Phase 1 diets were fed in a pellet form from d 0 to 10 after weaning, with Phase 2 diets fed in meal form from d 10 to 24. Fecal samples were collected on d 5, 9, 16, and 23. These samples were visually assessed and scored on a scale of 1 to 5 to determine consistency of the fecal samples then analyzed for DM. From d 0 to 10, neither sulfate addition to the water nor zeolite influenced ADG, ADFI, or F/G. Dietary treatment had no effect on fecal consistency; however, pigs drinking control water had a lower (P<0.01) fecal score (fewer visual observations of scours) than pigs drinking high-sodium sulfate water. From d 10 to 24, pigs drinking control water had improved (P<0.01) ADG, ADFI and F/G compared with pigs drinking high-sodium sulfate water. Dietary zeolite increased (linear, P<0.01) ADG and ADFI, but did not affect fecal scores. Similar to Phase 1, pigs drinking control water had lower (P<0.01) fecal scores, indicating less scouring compared with pigs drinking the high-sodium sulfate water. Dry matter analysis indicated that dietary zeolite had no effect on fecal DM, but high-sodium sulfate water decreased (P<0.01) total DM content of fecal samples in both Phase 1 and the first collection in Phase 2, but not on d 23, the final collection. Overall (d 0 to 24), increasing zeolite increased (linear, P<0.05) ADG and ADFI, but F/G was not affected. Pigs drinking high-sulfate water had decreased (P<0.01) ADG and ADFI and poorer (P<0.01) F/G compared with pigs drinking control water. In conclusion, pigs drinking water with 3,000 ppm sodium sulfate had decreased ADG, ADFI, and poorer F/G from d 10 to 24 and for the overall trial. These pigs also had an increased incidence of scouring as measured by lower fecal DM compared with pigs drinking control water. Although zeolite improved ADG and ADFI, it did not influence fecal consistency.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; Nursery pig; Sulfate; Water; Zeolite